Commemorating alternative organizations and marginalized spaces: The case of forgotten Finntowns. (January 2016) - Rodgers, Diane M.; Petersen, Jessica; Sanderson, Jill
Alternative organizations have become increasingly of interest in organizational theory. Previously understudied, these organizations have also been ignored or forgotten in the dominant narratives and spaces of commemoration. This further limits what we know about the past and the potential of alternative organizations. To illustrate this problem, we offer a specific case study of the forgotten alternative organizations and marginalized space of a former Finntown alongside the commemorative narratives and practices of capitalist entrepreneur heritage spaces. Extending organization theory on memory and forgetting, we detail how commemoration not only tends to legitimate capitalist forms of organizing, but also excludes alternatives. Finntowns, with their emphasis on cooperative organizations and community, provide a unique opportunity for organization studies to explore commemoration and forgetting in terms of power relations, time, and space. These marginalized spaces contained alternative organizations coexisting and contrasting with dominant capitalist organizations. Remembering their contributions means taking alternative organizations seriously, acknowledging their historic importance as well as their ability to be models for contemporary organizations.